Species-habitat relationship of the Red-winged Blackbird (Agelaius phoeniceus) in the Yucatan peninsula - Palma Cancino, Davira; Feldman, Richard; De León, Luis; Canto, Canto (Ecosistemas y Recursos Agropecuarios, 2022)
Acknowledging that a species’ association with habitat may varyamong phenological seasons, allows us to make predictions about how its distribution might respond to global change. In our study, we analyzed how habitatassociations for Red-winged Blackbird (Agelaius phoeniceus) varied between the breeding (May-July) and non-breeding (December-January) seasons in the Yucatan Peninsula, Mexico. We used eBird checklists to generate species detection/nondetection data and land cover classes and urban light intensity to indicate habitat type. We used Random Forest to model occurrence probability per season with detection/non-detection as the response variable and 13 land cover classes, two city light variables, and four measures of sampling effort as predictor variables. The predictors with the greatest contribution that were positively associated with occurrence were savannah, woody savannah, grassland, and wetland cover, the number of observers, and observation distance and duration. The predictors most negatively associated with occurrence were evergreen forest cover, city lights and observation start time. In both seasons the species occurred in coastal vegetationtypes (wetlands, savannahs, grasslands), and avoided urbanized areas and forest,suggesting that Red-winged Blackbird in the region is affected little by seasonality.
Keywords: Citizen science; distribution; ocurrence; seasonality; Random Forest